The Revolution According to Raymundo Mata as Narrative Transformation of the Philippines Revolution - OZAKI, MARIKO (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper takes a look at the narratives of the Philippine Revolution in a Philippine novel in English. Philippine novels about the revolution and the war against America describe the revolution as elites' initiation, and the masses are merely followers with no noble vision. The Revolution challenges such an elite-and-masses dichotomous relationship, and deconstructs what seems to be monolithic identity and linguistic background in which the narratives of the Filipinos are embedded. Doing so breaks down, whether consciously or not, the conventional notions of colonialism, state, nation and self, and in a sense detaches the subject from the material coacern and relation to the outside world. The Revolution reveals the shift of an attention from the customary search for a nation to poststructural deconstruction of such an aspiration. The celebration of ambiguous, uncertain and multi-vocal perceptions and languages in the novel replaces nation-bound vision and identity.